Larry Page’s Styles of Leadership - Rachmanantya, Anggita; Wahyuni, Sari; Nurrohman, Andi; Ralia, Anansya; Martono, Aniek (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2020)
Leaders are very important for organizations and businesses. The various characters of leaders can determine the success of an organization due to their role and responsibility for planning, organizing, and decision-making of organizational strategies to achieve their goals. One of the leaders whose characteristic is quite interesting and possibly become our role models is Larry Page, a co-founder of Google Inc. The researchers used qualitative research methods by descriptive research in explaining Larry Page style of leadership in leading Google Inc. Result of this study shows that Larry Page has a very open and equal way of leading, making him a democratic and transformational leader for an instance Larry believe in crazy ideas of their employees since he believes that insane ideas could change the world whereas not all the leaders can trust their subordinate. To hear the ideas, Larry always encourages his subordinate to speak up at every opportunity and instantly give them constructive feedback.